2020
DOI: 10.1136/jmedgenet-2019-106336
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic characterisation and phenotype correlation in von Hippel-Lindau (VHL) disease based on the Elongin C binding site: a large retrospective study

Abstract: BackgroundVon Hippel-Lindau (VHL) disease is an autosomal dominant genetic tumour syndrome resulting from mutations in the VHL gene lineage, and its prognosis is generally poor. This study aimed to provide a more valuable genotype–phenotype correlation based on the Elongin C binding site in VHL disease.MethodsThis study included 553 patients (194 families) who were diagnosed with VHL disease in our centre from September 2010 to February 2019. According to the type of gene mutation, the patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 78 Additionally, various mutation types in this gene were found to be associated with different prognoses among patients. 79 Interestingly, in this study, we unexpectedly observed a connection between different mutation locations in the VHL gene and the levels of certain DAMs in plasma ( Figures 8 , S3 ). Notably, distinct mutation locations resulted in variations in the same metabolite levels.…”
Section: Discussionmentioning
confidence: 53%
“… 78 Additionally, various mutation types in this gene were found to be associated with different prognoses among patients. 79 Interestingly, in this study, we unexpectedly observed a connection between different mutation locations in the VHL gene and the levels of certain DAMs in plasma ( Figures 8 , S3 ). Notably, distinct mutation locations resulted in variations in the same metabolite levels.…”
Section: Discussionmentioning
confidence: 53%
“…If the person has an uncle, cousin, or grandparent with VHL, they are also at risk for developing VHL. Moreover, it has been reported the presence of the disease in individuals without family background, therefore it is necessary a differential diagnosis in each individual [30].…”
Section: Inheritancementioning
confidence: 99%
“…However, all patients were enrolled in VHL-disease surveillance protocol. A large study, that included 533 patients with VHL disease, evaluated the correlation between developing VHL-related tumors and the type of VHL mutations [ 133 ]. The researchers found that truncating and missense mutations in non-Elongin-C binding sites conferred a high risk for the development of CNS hemangioblastomas.…”
Section: Clinical and Genetic Features Of Selected Manifestations Of ...mentioning
confidence: 99%